2021
DOI: 10.1111/apt.16392
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic risk on liver fibrosis in non‐alcoholic fatty liver disease as assessed by magnetic resonance elastography

Abstract: Background: Variants in multiple genetic loci modify the risk of non-alcoholic fatty liver disease (NAFLD) and cirrhosis but there are limited data on the quantitative impact of variant copies on liver fibrosis. Aim:To investigate the effect of PNPLA3, TM6SF2, MBOAT7, GCKR and HSD17B13 genotype on liver fibrosis assessed by magnetic resonance elastography (MRE), a reproducible, accurate, continuous biomarker of liver fibrosis.Methods: This is a cross-sectional analysis derived from a well-characterised cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…The primary hepatic effects of the I148M protein variant are most likely attributable to its repression of lipase activity [ 109 ], resulting in increased intracellular accumulation of triglycerides with the number of risk alleles (the G allele). In a recent study in which subjects were phenotyped by MRI-PDFF, each copy of the PNPLA3 risk allele was associated with a 2.56% increase in hepatic steatosis [ 110 ]. In addition, cumulative evidence also suggests that PNPLA3 is associated with fibrosis progression, development of HCC, ESLD, and all-cause mortality [ 111 ].…”
Section: Evolving Non-invasive Testsmentioning
confidence: 99%
“…The primary hepatic effects of the I148M protein variant are most likely attributable to its repression of lipase activity [ 109 ], resulting in increased intracellular accumulation of triglycerides with the number of risk alleles (the G allele). In a recent study in which subjects were phenotyped by MRI-PDFF, each copy of the PNPLA3 risk allele was associated with a 2.56% increase in hepatic steatosis [ 110 ]. In addition, cumulative evidence also suggests that PNPLA3 is associated with fibrosis progression, development of HCC, ESLD, and all-cause mortality [ 111 ].…”
Section: Evolving Non-invasive Testsmentioning
confidence: 99%
“…It is important to note that the rs626283 SNP is in strong linkage disequilibrium with rs641738 across numerous studies (23). Although the majority of large studies find a clear association between MBOAT7 loss of function and NAFLD progression, it is important to point out that not all studies have found statistically significant associations (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Although consistent trends in association exist, several independent studies looking at NAFLD-related indices in adults (24)(25)(26)(27)(28)(29)(30)(31) and children (32)(33)(34)(35) have failed to conclude that the rs641738 SNP is associated with NAFLD progression.…”
Section: Genetic Variation Near Mboat7 Confers Increased Susceptibili...mentioning
confidence: 99%
“…Although the majority of large studies find a clear association between MBOAT7 loss of function and NAFLD progression, it is important to point out that not all studies have found statistically significant associations (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Although consistent trends in association exist, several independent studies looking at NAFLD-related indices in adults (24)(25)(26)(27)(28)(29)(30)(31) and children (32)(33)(34)(35) have failed to conclude that the rs641738 SNP is associated with NAFLD progression. However, it is important to consider that a recent metaanalysis of all published studies including over 1 million subjects confirmed that the rs641738 variant is a risk factor for the presence and severity of NAFLD in individuals of European descent (36).…”
Section: Genetic Variation Near Mboat7 Confers Increased Susceptibili...mentioning
confidence: 99%
“…They concluded that average pre-gestational BMI, breastfeeding for at least six months and avoiding early supplementary formula milk feeding reduce the risk of NAFLD diagnosis by liver ultrasound[ 50 ]. Additionally, more extended maintenance of breastfeeding resulted in multiple benefits on maternal metabolism and a lower risk of NAFLD in mid-life[ 51 - 53 ].…”
Section: Environmental and Epigenetic Factors: Evidence In Experiment...mentioning
confidence: 99%